2017
DOI: 10.1371/journal.pone.0180561
|View full text |Cite
|
Sign up to set email alerts
|

Three distinct pneumotypes characterize the microbiome of the lung in BALB/cJ mice

Abstract: Bacteria can rarely be isolated from normal healthy lungs using conventional culture techniques, supporting the traditional belief that the lungs are sterile. Yet recent studies using next generation sequencing report that bacterial DNA commonly found in the upper respiratory tract (URT) is present at lower levels in the lungs. Interpretation of that finding is complicated by the technical limitations and potential for contamination introduced when dealing with low biomass samples. The current work sought to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Willis et al also found that up to 50% of the bacterial DNA from sinus tissue was derived from nonviable sources [20]. The traditional view that viable bacteria are rarely present in normal healthy lungs is consistent with the lungs being actively surveilled by immune cells and the observation that 30% of tissue samples were sterile in the Scheiermann and Klinman study [16]. In line with these findings, Segal et al reported that the bacterial DNA content in some human lung samples could not be distinguished from that of background/negative control samples [18].…”
Section: Viable and Nonviable Components Of Lung Microbiotamentioning
confidence: 75%
See 2 more Smart Citations
“…Willis et al also found that up to 50% of the bacterial DNA from sinus tissue was derived from nonviable sources [20]. The traditional view that viable bacteria are rarely present in normal healthy lungs is consistent with the lungs being actively surveilled by immune cells and the observation that 30% of tissue samples were sterile in the Scheiermann and Klinman study [16]. In line with these findings, Segal et al reported that the bacterial DNA content in some human lung samples could not be distinguished from that of background/negative control samples [18].…”
Section: Viable and Nonviable Components Of Lung Microbiotamentioning
confidence: 75%
“…Currently, it has been estimated that a ratio of bacteria to human cells in the body is close to 1:1 [75]. [13,[15][16][17][18]. It should be noted that different studies suggest that most bacterial DNA detected in the lungs might come from nonviable bacteria.…”
Section: Viable and Nonviable Components Of Lung Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…Given the ubiquitous use of mice in the study of inflammatory lung disease, it is crucial to determine the immunologic and biologic significance of variation in murine lung bacteria. One research group reported their difficulty in detecting lung bacteria in one-third of the healthy adult mice studied (49). Despite technical limitations to their approach (e.g., omitting quantification of total bacterial DNA burden, studying a single shipment of mice, using small sections of excised lung tissue rather than whole lungs, not using the touchdown PCR protocol preferred for low-biomass amplification [50]), the authors interpreted this lack of signal as evidence of lung sterility.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, healthy lungs were believed to be sterile-except for infections-since conventional culture techniques rarely isolated bacteria from them. However, with the advent of next-generation sequencing (NGS) technologies, a wide variety of bacterial DNA has been commonly detected in the lower respiratory tract of healthy individuals [8][9][10]. The lung microbiome is relatively low in biomass, with 10 3 to 10 5 bacteria per gram of tissue in healthy lungs [11].…”
Section: Introductionmentioning
confidence: 99%